(untitled) (University of Khartoum Engineering Journal, 2022)
Extreme hydrological events such as floods cause severe damage to the human society living along the rivers, Wadis and coastal areas. Reliable estimation of the magnitudes of these floods with various return periods, particularly in rivers and Wadis, is of great significance in minimizing flood damage and in designing hydraulic structures. This can be achieved through flood frequency analysis. This study aims at conducting flood frequency analysis for the Eastern Nile within Sudan. Annual maximum instantaneous flood peaks at seven stations were statistically analyzed and the underlying frequency distribution for each station was determined. Several flood frequency models have been tested, namely, Extreme Value type1, Two parameters Log Normal, Three parameters Log Normal and Person type III distribution. The selection of the best frequency model for a particular station was based on the Chi square test and minimum root mean square error. The parameters of the distributions have been determined by the method of L-moments. A regional analysis was then carried out using the Index Flood method. The results indicate that the seven stations can be grouped into two regions, namely the Blue Nile region and River Atbara region. Hence flood frequency curves were developed for the two regions.